2003
DOI: 10.1111/j.1572-0241.2003.07172.x
|View full text |Cite
|
Sign up to set email alerts
|

Volume and yield of screening colonoscopy at a tertiary medical center after change in medicare reimbursement

Abstract: Since the change in Medicare reimbursement, there has been a significant increase in the number and proportion of colonoscopies performed for screening at our institution. Patients screened since this change are older, and the detection rate of neoplastic lesions is similar to those previously screened for a family history of colorectal cancer or polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 21 publications
2
21
0
2
Order By: Relevance
“…7). Effective July 1, 2001, Medicare does provide coverage for screening colonoscopy for all individuals, not just those at increased risk of colorectal cancer (8). Previous evidence suggests that there is the potential for a 75% to 90% reduction in colorectal cancer mortality with the use of colonoscopy and clearing polypectomy, substantially higher than the 60% to 70% estimated for sigmoidoscopy and 20% to 60% estimated for fecal occult blood test (6,(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 82%
“…7). Effective July 1, 2001, Medicare does provide coverage for screening colonoscopy for all individuals, not just those at increased risk of colorectal cancer (8). Previous evidence suggests that there is the potential for a 75% to 90% reduction in colorectal cancer mortality with the use of colonoscopy and clearing polypectomy, substantially higher than the 60% to 70% estimated for sigmoidoscopy and 20% to 60% estimated for fecal occult blood test (6,(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 82%
“…Since that time, there has been a dramatic increase in the performance of screening colonoscopies. 8,9 Despite its utility, colonoscopy has inherent limitations, some of which are operator-dependent. Several published studies have reported colonoscopy adenoma miss rates ranging from 6% to 27%.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the quantity of routine endoscopic examinations has grown considerably because of an aging population and an increased subject awareness of the benefits of cancer screening (1,2). Upper and lower gastrointestinal (GI) endoscopic examinations have been recommended for first-line screening of cancer because of increasing safety.…”
Section: Introductionmentioning
confidence: 99%